Integrated safety of levodopa‐carbidopa intestinal gel from prospective clinical trials. Issue 4 (23rd December 2015) - Lang, Anthony E.; Rodriguez, Ramon L.; Boyd, James T.; Chouinard, Sylvain; Zadikoff, Cindy; Espay, Alberto J.; Slevin, John T.; Fernandez, Hubert H.; Lew, Mark F.; Stein, David A.; Odin, Per; Fung, Victor S.C.; et al.
ABSTRACT: Background: Continuous administration of levodopa‐carbidopa intestinal gel (carbidopa‐levodopa enteral suspension) through a percutaneous endoscopic gastrojejunostomy is a treatment option for advanced Parkinson disease (PD) patients with motor fluctuations resistant to standard oral medications. Safety data from 4 prospective studies were integrated to assess the safety of this therapy. Methods: Safety data from 4 studies were summarized using 2 overlapping data sets, permitting the separation of procedure/device–associated (n = 395) from non‐procedure/device adverse events (n = 412). Results: At the data cutoff, median exposure to levodopa‐carbidopa intestinal gel was 911 days (range, 1‐1980 days) with 963 total patient‐years of exposure. Procedure/device adverse events occurred in 300 patients (76%), and serious adverse events occurred in 68 (17%); most frequently reported procedure/device adverse events and serious adverse events were complications of device insertion (41% and 8%, respectively) and abdominal pain (36% and 4%, respectively). Non‐procedure/device adverse events occurred in 92% (379), with most frequently reported being insomnia (23%) and falls (23%); 42% (171) had non‐procedure/device serious adverse events, with most frequently reported being pneumonia (5%) and PD symptoms (2%). Adverse events led to discontinuation in 17% (72), most frequently because of complication of device insertion (2.4%). There were 34 treatment‐emergent deaths (8.3%) in the overlapping data sets, 2 of which (0.5%) were considered "possibly related" to the treatment system. Conclusion: In the largest collection of levodopa‐carbidopa intestinal gel safety data from prospective clinical studies, procedure/device events were frequently reported and occasionally life threatening. Most non‐procedure/device events were typical for levodopa treatment and an elderly population. These factors combined with high treatment efficacy led to a relatively low discontinuation rate in advanced PD patients. © 2015 International Parkinson and Movement Disorder Society